2014
DOI: 10.1186/s13059-014-0536-6
|View full text |Cite
|
Sign up to set email alerts
|

TNFα signalling primes chromatin for NF-κB binding and induces rapid and widespread nucleosome repositioning

Abstract: BackgroundThe rearrangement of nucleosomes along the DNA fiber profoundly affects gene expression, but little is known about how signalling reshapes the chromatin landscape, in three-dimensional space and over time, to allow establishment of new transcriptional programs.ResultsUsing micrococcal nuclease treatment and high-throughput sequencing, we map genome-wide changes in nucleosome positioning in primary human endothelial cells stimulated with tumour necrosis factor alpha (TNFα) - a proinflammatory cytokine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 54 publications
(77 reference statements)
3
50
0
Order By: Relevance
“…In human endothelial cells, proinflammatory stimulation is linked to both acute and chronic disorders (Libby et al 2011;Brown et al 2014), and we previously used these cells to characterize the dynamic clustering of NF-κB-regulated genes in 3D space , and global chromatin "priming" prior to NF-κB-dependent transcription (Diermeier et al 2014). Here, we study the still-elusive properties of how the new proinflammatory transcriptional program is integrated in the pre-existing one in 3D space and over time.…”
mentioning
confidence: 99%
“…In human endothelial cells, proinflammatory stimulation is linked to both acute and chronic disorders (Libby et al 2011;Brown et al 2014), and we previously used these cells to characterize the dynamic clustering of NF-κB-regulated genes in 3D space , and global chromatin "priming" prior to NF-κB-dependent transcription (Diermeier et al 2014). Here, we study the still-elusive properties of how the new proinflammatory transcriptional program is integrated in the pre-existing one in 3D space and over time.…”
mentioning
confidence: 99%
“…While NF-B is not thought to be a 'pioneering factor', i.e. a transcription factor able to initiate chromatin remodelling, evidence does support a role for the factor in changing the nucleosome landscape at activated loci [33,34]. The second most enriched motif in IL-1 increased accessible regions was IRF1, interferon regulatory factor 1, a factor that increases with IL-1 stimulation [35].…”
Section: Discussionmentioning
confidence: 99%
“…Exciting new work from Diermeier et al has shown that TNF-α signaling directly changes chromatin structure around NF-κB-associated gene regions [191]. MAPK signaling has been shown to be required for IL-1β production in DCs [189] and MHCII expression in macrophages [192].…”
Section: Future Direction: ‘Training’ Of Dendritic Cells Against C Nmentioning
confidence: 99%